Gandrung Dance Training for Teenagers in Perampuan Village, West Lombok Regency - Baiq Larre Ginggit Sekar wangi; Taufik Mawardi; Muharis Muharis; Lalu Guruh Virgiawan Dwi Kukuh; Muhammad Taufik (Jurnal Pengabdian Teratai, 2025)
This community service activity aims to increase the knowledge, skills, and interest of young people in traditional arts through Gandrung Dance Training in Perampuan Village, West Lombok Regency. The background of this activity is the declining interest of the younger generation in traditional Sasak dance, which is due to the dominance of popular culture, changes in lifestyle, and limited space for arts education in the community. In fact, Gandrung Dance has noble values that reflect the identity, social harmony, and philosophy of life of the Sasak people that are worth preserving. The method for implementing the activity uses a participatory approach, placing participants as active subjects in the learning process. The stages of the activity include: (1) orientation to introduce the concept and cultural values of Gandrung Dance, (2) demonstration of fourteen basic movement forms, (3) direct practice in groups with intensive guidance, (4) performance evaluation based on aspects of wiraga, wirama, and wirasa, and (5) final reflection to assess the understanding and experience of participants. Evaluation of the results is carried out through performance observation, pre- and post-training questionnaires, and reflective interviews. The results of the activity showed significant improvements in three main aspects: knowledge of the history and values of the Gandrung Dance increased from 35% to 90%; movement skills increased from 20% to 85%; and interest in preserving local culture increased from 25% to 88%. Furthermore, the training had a positive impact on participants’ social attitudes, such as increased self-confidence, discipline, and the ability to work together. This activity demonstrated that traditional arts training based on local culture effectively strengthens adolescent character and builds awareness of cultural preservation in the community